2023
DOI: 10.3390/md21060324
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intestinal Barrier on Alleviating an Increase in Blood Pressure by Sodium Alginate Intake in 2-Kidney, 1-Clip Renovascular Hypertensive Rats

Abstract: Sodium alginate (SALG) is a substance derived from brown seaweed that has been shown to reduce blood pressure (BP). However, its effects on renovascular hypertension caused by 2-kidney, 1-clip (2K1C) are not yet clear. Previous research suggests that hypertensive rats have increased intestinal permeability, and that SALG improves the gut barrier in inflammatory bowel disease mouse models. Therefore, the goal of this study was to determine whether the antihypertensive effects of SALG involve the intestinal barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…A previous report showed that the administration of potassium alginate lowered BP in SHRs and induced changes in gut microbiota [ 10 ]. As well, we previously observed that the intake of sodium alginate lowered BP in 2K1C rats and restored intestinal barrier function [ 11 ]. Furthermore, it was reported that alginate, fucoidan, and laminaran, when administered separately, altered the gut microbiota in normotensive rats and modulated the concentration of metabolites in the intestines [ 10 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…A previous report showed that the administration of potassium alginate lowered BP in SHRs and induced changes in gut microbiota [ 10 ]. As well, we previously observed that the intake of sodium alginate lowered BP in 2K1C rats and restored intestinal barrier function [ 11 ]. Furthermore, it was reported that alginate, fucoidan, and laminaran, when administered separately, altered the gut microbiota in normotensive rats and modulated the concentration of metabolites in the intestines [ 10 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 75%
“…Alginate, one of the main components of SJ, has been observed to suppress BP elevation in SHRs or 2K1C rats, respectively [ 10 , 11 , 60 ]. It has been reported that promoting sodium excretion is a potential mechanism for the effect of potassium alginate ingestion in suppressing the increase in BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertensive rat treatment with fucoidan resulted in a persistent reduction of high blood pressure, with mechanisms that might involve an endothelial-protective function mediated by the Akt-eNOS signalling pathway [78]. In addition, the algal polysaccharides alginate, in both potassium and sodium form, has established anti-hypertensive activity, as demonstrated in spontaneous and induced rat models of hypertension [79][80][81][82][83], both as a scaffold for potassium delivery [79] and as an active molecule [80][81][82][83]. This effect was associated with low cardiovascular and renal damage [81] and downregulation of heart failure markers [82], and is likely due to a modulation of the gut microbiota and an improvement of the gut barrier [82,83] (Table 1).…”
Section: Pre-clinical In Vivo Studies On Marine Compounds For Cvds Tr...mentioning
confidence: 99%
“…In addition, the algal polysaccharides alginate, in both potassium and sodium form, has established anti-hypertensive activity, as demonstrated in spontaneous and induced rat models of hypertension [79][80][81][82][83], both as a scaffold for potassium delivery [79] and as an active molecule [80][81][82][83]. This effect was associated with low cardiovascular and renal damage [81] and downregulation of heart failure markers [82], and is likely due to a modulation of the gut microbiota and an improvement of the gut barrier [82,83] (Table 1). ACAT-acyl-coenzyme A:cholesterol acyl-transferase; ACE-angiotensin converting enzyme; COX1-cyclooxigenase 1; DOCA-deoxycorticosterone acetate; eNOS-endothelial nitric oxide synthase; NOX-4-NADPH oxydase 4; ICAM-1-intercellular adhesion molecule-1; LXR-β-liver X receptor beta; mPTP-mitochondrial permeability transition pore; PI3K-phosphatidyl inositol 3-kinase; NF-κB-nuclear factor kappa B; FGF-fibroblast growth factor; VEGF-vascular endothelial growth factor; BDNF-brain-derived neurotrophic factor; SREBP-2-sterol regulatory element-binding protein 2; PPARα-peroxisome proliferator activated receptor alpha; ERK-extracellular signal-regulated kinase; TXB2-thromboxane B2; VCAM-1-vascular cell adhesion molecule-1.…”
Section: Pre-clinical In Vivo Studies On Marine Compounds For Cvds Tr...mentioning
confidence: 99%